Reductive Pentose Phosphate Cycle and Oxidative Carbohydrate Metabolic Activities in Pea Chloroplast Stroma Extracts - Furbank, Robert T. (1981)
Oxidative and reductive carbohydrate metabolism was studied in reaction mixtures based on chlorophyll-free stromal extracts from chloroplasts of Pisum sativum. A new assay system for the reductive pentose phosphate cycle was characterized. When provided with ATP, an enzymic ATP-regenerating system and reduced pyridine nucleotide, substantial rates of CO(2) fixation and pyridine nucleotide oxidation were observed following the addition of millimolar concentrations of reductive pentose phosphate cycle intermediates. The reduced pyridine nucleotide requirement could be met either by NADPH, or by NADH plus the added enzymes NAD(+)-glyceraldehyde phosphate dehydrogenase and phosphoglycerate kinase. When the assay system was primed with small amounts of reductive pentose phosphate cycle intermediates, lower rates of pyridine nucleotide oxidation were observed, but turnover of the complete cycle was demonstrated. Autocatalytic effects were not evident. The optimum pH and Mg concentrations for cycle turnover were similar to those believed to exist in the stroma of intact chloroplasts in the light. Oxidative carbohydrate metabolism was studied by supplying oxidized pyridine nucleotide and measuring its rate of reduction in the presence of sugar phosphates. Glycolytic activity, estimated as the rate of fructose-6-phosphate entry to the phosphofructokinase reaction was 2.7 micromoles per milligram chlorophyll per hour when fructose-6-phosphate was provided as substrate. Evidence based on glucose-6-phosphate and ribose-5-phosphate-dependent NADP(+) reduction showed that the oxidative pentose phosphate cycle was also active. Apparent oxidative pentose phosphate cycle turnover in the presence of ribose-5-phosphate, estimated as the rate of glucose-6-phosphate entry to the glucose-6-phosphate dehydrogenase reaction, was 1.7 micromoles per milligram chlorophyll per hour. It was concluded that under the defined conditions, reductive pentose phosphate cycle activity could be measured without interference from oxidative carbohydrate metabolism in this experimental system.